Studi Hadis Larangan Laki-Laki Memakai Baju Merah dan Kuning serta Korelasinya dengan Psikologi Warna - Endah Panghegar (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Clothing is something that a person wears or wears in various sizes tailored to the needs of the wearer. Clothing can provide a role and meaning in social life, although basically for a Muslim clothing has the main use to cover the aurat. As Muslims we make the Prophet as a role model including dressing for men. The purpose of this study is to determine the quality and understanding of the Hadith on the prohibition of men wearing red and yellow clothes and its correlation with colour psychology. Then it is expected to bring benefits to add insight and understanding. This research is classified as qualitative research of a library nature (Library Research), using the Maudhu'I method or thematic study, which is useful for examining the quality of the hadith and the contextual hadith to determine the understanding of the hadith. For the first step the author traces the hadith in the book Mu'jam al-Mufahras li Alfadz al-Hadis. Then, the source book of the hadith is referred to, after which the takhrij of the hadith is conducted to determine the quality of the traditions studied using the Maudhu'i method. Furthermore, the interpretation of the hadith is done by analysing the understanding of the hadith with a socio-historical approach and understanding its relationship with colour psychology. Regarding the understanding of the Hadith about the prohibition of men wearing red and yellow clothes, the prohibition is not absolute, some of the reasons for the prohibition at that time included imitating the identity of a people such as non-Muslims or women's groups and a form of boasting that was feared to cause arrogance, because psychologically also red and yellow are colours that attract attention around.